Mushkilāt Ta‘līm Mahārah al-Kalām li-Ṭullāb al-Ṣaff al-Ḥādī ‘Ashara fī al-Madrasah al-‘Āliyyah al-Islāmiyyah al-Khāmisah Jombang - Maghfurotul Laili; Mu’at (Program Studi Pendidikan Bahasa Arab, 2023)
Speaking skill is one of the language skills taught by students in learning Arabic. The aims of this study were (1) to find out how to teach speaking skills in class XI at Madrasah Aliyah Negeri 5 Jombang, (2) to find out the problems that exist in learning speaking skills in class XI at Madrasah Aliyah Negeri 5 Jombang, (3) to find solutions to overcome problems in learning speaking skills in class XI at Madrasah Aliyah Negeri 5 Jombang. This study uses qualitative research with a descriptive approach. Data obtained by Observation, Interview, and Documentation methods. The results of the research are (1) for teaching learning to use direct in methods and teachers also use audio-visual media such as short films, video conversations using Arabic. (2) the problems in this learning are the lack of understanding in learning speaking skills, educational background factors, the lack of students' desire to memorize vocabulary, and time constraints. (3) the solution to this problem in learning is the need for several strategies, methods and media for student learning, increasing vocabulary memorization by making cellphones a learning resource such as looking for vocabulary videos accompanied by songs and pictures, the teacher provides motivation to students by There is an Arabic language club.